1989
DOI: 10.2165/00003088-198916030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Tianeptine and its Main Metabolite

Abstract: The effect of chronic alcoholism (with or without associated moderate cirrhosis) on the disposition of the antidepressant tianeptine, which is devoid of substantial first-pass metabolism, was examined in 21 patients and 11 age-matched controls. Pharmacokinetic parameters for tianeptine and its C5 acid analogue metabolite (MC5 metabolite) were estimated by non-compartmental analysis. The area under the curve (AUC) for tianeptine, following a 12.5mg single oral dose, was decreased by 31% in chronic alcoholics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Tianeptine is an opioid agonist that is used clinically to treat depression (Kasper & McEwen, 2008 ), with a low incidence of poisoning or overdose reports (El Zahran et al, 2018 ). Tianeptine has lower affinity than oliceridine (~400 nM), but also has rapid brain distribution (with peak levels at 5 min) and rapid clearance through beta‐oxidation (Couet et al, 1990 ; Royer et al, 1988 ; Samuels et al, 2017 ) (undetected in plasma or brain 1 h after administration) consistent with the potency and duration of the respiratory depressant effect observed here. A recent study has investigated the respiratory depressant effects of tianeptine in male Swiss‐Webster mice and showed that at 100 mg·kg −1 the effects of tianeptine were sustained (over 80 min), but reversible by the antagonist naloxone (Baird et al, 2022 ).…”
Section: Discussionsupporting
confidence: 78%
“…Tianeptine is an opioid agonist that is used clinically to treat depression (Kasper & McEwen, 2008 ), with a low incidence of poisoning or overdose reports (El Zahran et al, 2018 ). Tianeptine has lower affinity than oliceridine (~400 nM), but also has rapid brain distribution (with peak levels at 5 min) and rapid clearance through beta‐oxidation (Couet et al, 1990 ; Royer et al, 1988 ; Samuels et al, 2017 ) (undetected in plasma or brain 1 h after administration) consistent with the potency and duration of the respiratory depressant effect observed here. A recent study has investigated the respiratory depressant effects of tianeptine in male Swiss‐Webster mice and showed that at 100 mg·kg −1 the effects of tianeptine were sustained (over 80 min), but reversible by the antagonist naloxone (Baird et al, 2022 ).…”
Section: Discussionsupporting
confidence: 78%
“…8,9 Tianeptine interacts highly (95%) with the plasma protein human serum albumin (HSA) because of the presence of the acid portion which reflects a poor volume of distribution. 10,11 Although the amino acid chain can be easily modified, the only ester derivative present in the literature 9 is its ethyl ester, first synthesized by French researchers.…”
Section: Introductionmentioning
confidence: 99%